Analyzing Adherence to the 2016 Infectious Diseases Society of America Guidelines for Candidemia in Cancer Patients. (22nd October 2022) - Lehmann, Dena M; Cohen, Nina; Lin, I-Hsin; Alexander, Shane; Kathuria, Ritu; Kerpelev, Marina; Taur, Ying; Seo, Susan K
Abstract: Background: Candidemia is associated with morbidity and mortality in cancer patients. We analyzed adherence to the 2016 Infectious Diseases Society of America (IDSA) candidiasis guidelines and the reasons for guideline nonadherence. We also investigated whether matrix-assisted laser desorption/ionization–time of flight (MALDI-TOF) improved time to effective antifungal therapy compared with historical data (median, 43.2 hours). Methods: Cancer patients with candidemia between 1/1/17 and 12/31/19 were included. Adherence to 7 individual IDSA guideline components was assessed. Composite IDSA guideline adherence (defined as meeting ≥6 guideline components) was also assessed. Charts were reviewed to examine reasons for noncompliance. Results: Of 157 patients with candidemia, 150 (95.5%) had infectious disease (ID) consultation. The median total time from blood culture collection to antifungal initiation was 42.1 hours. Excluding 39 patients with short treatment due to death, there was 100% adherence with surveillance blood cultures, followed by antifungal susceptibility testing (117/118, 99.2%), initial appropriate therapy (117/118, 99.2%), antifungal duration (110/118, 93.2%), line removal (82/91, 90.1%), eye exams (93/118, 78.8%), and step-down therapy (69/94, 73.4%). A quarter (30/118) did not meet composite IDSA guideline adherence. Univariate logistic regression suggested a relationship between poor cancer prognosis and incomplete adherence to the 2016 IDSA candidiasis guidelines (odds ratio, 8.6; 95% CI, 1.6–47). Conclusions: The addition of MALDI-TOF did not shorten time to effective antifungal therapy. Nearly all patients were seen by ID for candidemia. Poor cancer prognosis was a common factor for incomplete composite adherence to the 2016 IDSA candidiasis guidelines.